2015
DOI: 10.1002/jhet.2367
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Synthesis of Enamino‐Coumarin Derivatives Identified as Potent Antitumor Agents

Abstract: The reaction of 4‐aminocoumarin (2) with benzaldehyde gave the bisenamino derivatives 4. Thus, transamination of 2 with o‐phenylenediamine furnished enamino skeleton 3, which can be obtained from 1. Reaction of 1 with 5‐aminoisoxazole afforded 5. While reaction of 2 with benzalaniline, isatinanil and phenyl isothio cyanate afforded the corresponding 7, 8 and 9, respectively. Heterocyclic annulations of 2‐phenylthiazolidine‐4‐one 10 2‐phenylthiazolidin‐4‐one 10 and 2‐phenyl‐thiazinan‐4‐one 11 systems were achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…120,128 T3P 159 has been shown to work with N-acetylcysteine as the thioacid. 93,117,133 Acid catalysis has also been used. Acids used include ZnCl 2 134 and TsOH.…”
Section: Methodsmentioning
confidence: 99%
“…120,128 T3P 159 has been shown to work with N-acetylcysteine as the thioacid. 93,117,133 Acid catalysis has also been used. Acids used include ZnCl 2 134 and TsOH.…”
Section: Methodsmentioning
confidence: 99%
“…Ibrahim et al reported that the reaction of 4-aminocoumarin (5) with chloroacetic acid resulted in 1,2-dihydrochromeno [4,3-b]pyrrole-3,4-dione (22) in 58% yield (Scheme 7). This compound was studied for cytotoxic activity and found to be 1.5-fold more toxic than the standard 5-fluorouracil [75].…”
Section: Synthesis From Aminocoumarin Derivativesmentioning
confidence: 99%